An Evidence-based Pathway for Body Dysmorphic Disorder in Facial Aesthetics - Mandavia, Rishi; D'Souza, Hanna; Rupasinghe, Thiara; Cariati, Massimiliano; Mandavia, Tatiana (Facial Plastic Surgery, 2024)
Aesthetic procedures should be avoided in patients with body dysmorphic disorder (BDD) since they can negatively impact mental health and lead to further aesthetic dissatisfaction. There are no evidence-based patient pathways for BDD in facial aesthetics which can result in the failure to identify patients with BDD, leading to unsuitable treatments and suboptimal patient care. We aim to construct the first evidence-based patient pathway for BDD in surgical and nonsurgical facial aesthetics. A systematic review was performed and articles that discussed screening or patient pathways for BDD in field of facial aesthetics were included. We extracted relevant information from each article on screening tools and pathways for BDD. Data were synthesized by summarizing the data under column headings into a structured narrative and into new tables. Based on this synthesis, a practical pathway for BDD was constructed. Forty articles fulfilled the criteria for inclusion. Twenty-eight BDD screening tools were discussed in the included articles, and we provide an overview of these tools. Thirty-one articles discussed patient pathways for BDD, and we synthesized this information into a structured narrative. Combining these findings, we present an evidence-based patient pathway for BDD for patients presenting for facial aesthetic treatments. This systematic review has resulted in the first, evidence-based, patient pathway for BDD in surgical and nonsurgical facial aesthetics. This practical pathway can be used by aesthetic clinicians to identify patients with potential BDD and provide clear guidance for managing cases where BDD is suspected. It will help reduce the number of facial aesthetic procedures performed on patients with BDD, safeguard patient mental well-being, and prevent further aesthetic dissatisfaction.
Keywords: facial aesthetics; body dysmorphia; screening; pathway